Do energy prices put the tourism sector at risk? - Georgia Poutakidou; Angeliki N. Menegaki (Economies, 2023)
This paper studies the effect of a shock in the hospitality sector, namely the energy price increase, with stated preference methods and performs the subsequent analysis with a mixture of quantitative and qualitative tools. The hospitality sector is very important and is the backbone of the tourism industry worldwide. We designed and administered two semi-structured anonymous questionnaires that were sent randomly to recipients for completion. One questionnaire investigated tourists' behavior, visit and their stay and their spending intentions, whereas the second questionnaire investigated the hoteliers/managers estimations and beliefs on energy price increases and whether or how this price increase would have an effect on tourists' behavior and their visit, stay and spending intentions in the destination. Through two surveys, we collected answers to questions for three consecutive years-2021: representing the past/before the energy crisis, 2022: the present/the time of the crisis breakout and 2023: the future/after the crisis outbreak. Overall, a lower tourist expenditure is found for the future due to the energy price shock, but there are no significant differences between the answers of the two groups. Our results are insightful for tourism policy makers, hoteliers and managers and particularly those economies that rely heavily on tourism, e.g., island economies.
Keywords: 330; energy prices; hospitality; risk; survey; tourism